SOCIAL NETWORK ANALYSIS ON LEAN PRODUCTION AND WORLD CLASS MANUFACTURING: HOW ARE ASSOCIATED IN THE LITERATURE? - Goes, Gustavo Antiqueira [UNESP]; Satolo, Eduardo Guilherme [UNESP]; Queiroz, Timoteo Ramos [UNESP]; Correa Bernardo, Cristiane Hengler [UNESP]; Martins Raymundo, Juliana Delgado [UNESP] (Inst Federal Educacao, Ciencia & Tecnologia Sao Paulo, 2017)
This paper aims to conduct a Systematic Literature Review (SLR) to identify how to configure the publications that relate WCM and Lean Production issues. Therefore, a search on the Brazilian metasearch portal called CAPES Periodicals was conducted focusing on articles of the last five years. They were identified after screening and filtering a total of 42 articles, which were analyzed. The construction of the network analysis has identified that the issues are still in an initial phase of association, with the characteristic part of decentralizes networks, with some points of greatest association. It was also identified that the theme Lean Production has greater representation between the two topics due its higher use by authors.
Keywords: Interrelation; Social networks; Systemic literature review